2018
DOI: 10.1038/s41467-018-07467-5
|View full text |Cite|
|
Sign up to set email alerts
|

Exocyst dynamics during vesicle tethering and fusion

Abstract: The exocyst is a conserved octameric complex that tethers exocytic vesicles to the plasma membrane prior to fusion. Exocyst assembly and delivery mechanisms remain unclear, especially in mammalian cells. Here we tagged multiple endogenous exocyst subunits with sfGFP or Halo using Cas9 gene-editing, to create single and double knock-in lines of mammary epithelial cells, and interrogated exocyst dynamics by high-speed imaging and correlation spectroscopy. We discovered that mammalian exocyst is comprised of tetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
104
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 55 publications
16
104
1
2
Order By: Relevance
“…Additionally, isolated COG subcomplexes show lobe‐specific pattern of interaction with different protein partners including β‐COP, p115, and STX5 . The COG complex assembly/disassembly model is in good agreement with several models proposed for the mammalian exocyst .…”
Section: Cog Complex Function In Golgi Trafficking and Glycosylationsupporting
confidence: 75%
“…Additionally, isolated COG subcomplexes show lobe‐specific pattern of interaction with different protein partners including β‐COP, p115, and STX5 . The COG complex assembly/disassembly model is in good agreement with several models proposed for the mammalian exocyst .…”
Section: Cog Complex Function In Golgi Trafficking and Glycosylationsupporting
confidence: 75%
“…Recent structural studies show that exocyst consists of two subcomplexes with equal stoichiometry, and the connectivity among the subunits is conserved between budding yeast and mouse. Subcomplex I (SC I) consists of Sec3, Sec5, Sec6, and Sec8; whereas Sec10, Sec15, Exo70, and Exo84 are assembled into SC II (Figure , in box) . Furthermore, live cell imaging of CRISPR‐mediated exocyst subunit‐superfolder green fluorescent protein (sfGFP) knock‐in cells showed that each subcomplex can arrive at the PM without its partner subcomplex, even though ≈65% of SC I are associated in the cytoplasm .…”
Section: How Is the Exocyst Complex Assembled?mentioning
confidence: 99%
“…Subcomplex I (SC I) consists of Sec3, Sec5, Sec6, and Sec8; whereas Sec10, Sec15, Exo70, and Exo84 are assembled into SC II (Figure , in box) . Furthermore, live cell imaging of CRISPR‐mediated exocyst subunit‐superfolder green fluorescent protein (sfGFP) knock‐in cells showed that each subcomplex can arrive at the PM without its partner subcomplex, even though ≈65% of SC I are associated in the cytoplasm . These observations suggest that distinct regulators might control each subcomplex and their association with one another.…”
Section: How Is the Exocyst Complex Assembled?mentioning
confidence: 99%
See 2 more Smart Citations